Cultural Shock and its Recovery as Seen through Language Features in Emily in Paris - Bryan Edbert (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
This study aims to find out the language features used by Emily Cooper in the series Emily in Paris during the culture shock and recovery stages. In conducting this study, I used the theory of cross-cultural transition and adaptation stages by Oberg (1960), as cited in Marx (2001), and the theory of language features by Lakoff (2004) and Coates (2004). This study was done using a qualitative approach in which I transcribed and analyzed Emily Cooper’s utterances that occurred in all office scenes in Paris. Emily used adjectives, hedges, intensifiers, grammar, politeness, swear words, commands and directives, minimal responses, and questions language features during the culture shock stage. Emily used color terms, adjectives, hedges, intensifiers, grammar, politeness, swear words, minimal responses, and questions language features during the recovery stage. Emily’s personality, conversation context, and culture were variables that might influence Emily’s use of language features. Keywords: language features, cultural adaptation, culture shock, recovery